Corporate ESG Responsibility, External Supervision, and Corporate Reputation - Kong, Xiangxin (Transactions on Economics, Business and Management Research, 2024)
This article takes A-share listed companies from 2014 to 2023 as samples, takes the fulfillment of corporate ESG responsibilities by listed companies as the independent variable, empirically tests its impact on corporate reputation, and introduces three variables: media attention, analyst attention, and institutional shareholding as proxy variables for external supervision. It deeply explores the impact of external supervision from different perspectives on the impact of corporate ESG responsibilities on reputation. The research results indicate that (1) Fulfilling ESG responsibilities can significantly affect a company’s reputation. Enterprises that fulfill ESG responsibilities better often have a better reputation. (2) If a company receives stronger media attention, it will strengthen the promotion effect of ESG responsibility on its reputation. (3) The more analysts who track a company, the stronger the promotion effect of ESG responsibility on reputation. (4) The higher the shareholding ratio of corporate institutions, the better the ESG performance of the enterprise can enhance its reputation. After conducting robustness tests using methods such as replacement measurement, instrumental variable method, and GMM, the conclusion still holds.